Tortor Somba: Kajian Teologis Ritual Kematian Saur Matua pada Masyarakat Batak Toba di Desa Tomok Parsaoran - Santa Jojor Banjarnahor; Meditatio Situmorang; Bestian Simangunsong; Hanna Dewi Aritonang; Benhardt Siburian (Jurnal Teologi Injili dan Pendidikan Agama, 2025)
This paper discusses the theological study of tortor somba in the death ceremony of saur matua in the Batak Toba community. Tortor somba is believed to be able to realize the bond of brotherhood between those present in the death ceremony of a perfect person in kinship. The person is called saur matua, which means complete or perfect, namely a person who has had children and grandchildren, and has succeeded in life both socially and materially. Tortor somba is also believed to be a sign of respect, welcoming those who have a higher position, with this respect can receive blessings. The purpose of this study is to explore the meaning of tortor somba in the death ritual of saur matua in the Batak Toba community, as well as to determine the theological views on the death ritual of saur matua in the Batak Toba community. The research method in this researcher uses a qualitative research method with an ethnographic approach by conducting interviews with one of the village officials, three people representing the Batak Toba community, three traditional leaders, one HKBP Pastor, one GKPI Pastor, and one Catholic Tomok Pastor. The data was studied to examine theological studies regarding tortor somba in the saur matua death ceremony in the Toba Batak community.The results of the research show that the meaning of tortor somba in the Saur Matua death ceremony in the Toba Batak community is a form of pride, respect, and also gratitude. Tortor somba in death ceremonies is not only a child's form of respect for their deceased parents, but also to honor the spirits of ancestors or forefathers. This expression of respect is intended for ancestors. It is also important to provide new knowledge to the younger generation that tortor somba must be based on and illuminated by the word of God in order to maintain and respect culture, because if understood properly and correctly, religion and culture will complement each other.